2012
DOI: 10.1108/17581181211230694
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative production of pedagogical knowledge: enhancing students’ learning

Abstract: Purpose -The purpose of this paper is to investigate students' qualitatively different ways of understanding basic economic relationships in three undergraduate courses in the discipline of accounting. Design/methodology/approach -The theoretical frame is variation theory, which is a learning theory about the different ways students understand the learning object (in this study, basic economic relationships). The instructors chose a learning object which was investigated under two different teaching conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Additionally he participated in the discussions using Socratic questions to encourage collaboration and critical thinking between the students. Rovio-Johansson and Lumsden (2012) found that using collaborative study groups helped students improve their learning, at a business school in Sweden. The designed an experiment with business school students to test the effectiveness of collaborative study groups called a "learning study model" (Rovio-Johansson and Lumsden, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally he participated in the discussions using Socratic questions to encourage collaboration and critical thinking between the students. Rovio-Johansson and Lumsden (2012) found that using collaborative study groups helped students improve their learning, at a business school in Sweden. The designed an experiment with business school students to test the effectiveness of collaborative study groups called a "learning study model" (Rovio-Johansson and Lumsden, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rovio-Johansson and Lumsden (2012) found that using collaborative study groups helped students improve their learning, at a business school in Sweden. The designed an experiment with business school students to test the effectiveness of collaborative study groups called a "learning study model" (Rovio-Johansson and Lumsden, 2012). This model used collaborative learning theory to help students apply "variation theory," which is a learning theory about the different ways students understand the quantitative subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…CL participation boosts learners in critical thinking through problem-solving process, enhancing them more in drill-practice skills (Maesin et al, 2009). CL contributes to learners' performance and improves their learning process as well (Rovio-Johansson and Lumsden, 2012). In addition, CL can also help learners to prepare for their exams with more confidence as stated by Picou (2011).…”
Section: Benefits and Challenges Of Collaborative Learningmentioning
confidence: 98%